Country Stress Events : Does Governance Matter? - Kochanova, Anna (IMF Working Papers; Working Paper ;, 2012)
This paper analyzes the linkages between governance quality and country stress events. It focuses on two types of events: fiscal and political stress events, for which two innovative stress indicators are introduced. The results suggest that weaker governance quality is associated with a higher incidence of both fiscal and political stress events. In particular, internal accountability, which measures the responsiveness of governments to improving the quality of the bureaucracy, public service provision, and respect for the institutional framework in place, is positively associated with fiscal stress events. However, external accountability, which captures government accountability before the public in general, through elections and the democratic process, seems to be more important for political stress events. These results hold when using balanced country samples where region, oil-exporter status, income level, and time are taken into account.